English - Vulević, Marko (Political Life, 2026)
This paper analyzes the dominance and eventual collapse of Montenegro’s Democratic Party of Socialists (DPS) through the lens of dominant party theory. For three decades, DPS governed without alternation, blurring the line between competitive democracy and a de facto one-party state. The study examines mechanisms of dominance (patronage, institutional capture, and identity politics), alongside internal weaknesses, public discontent, and external influences that culminated in the party’s 2020 defeat. Situating Montenegro in comparative perspective, the paper highlights parallels and divergences with other predominant party systems in the Balkans and beyond, contributing to debates on hybrid regimes and democratic resilience.